ANALISIS PENERAPAN GOOD GOVERNANCE DALAM PENGELOLAAN KEUANGAN DESA PADA DESA HEGARMANAH KABUPATEN SUKABUMI - Trisanti, Miana; Prihatni, Rida; Nasution, Hafifah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze the application of good governance in managing village finances. In addition, this research was conducted to analyze the constraints on the implementation of good governance, as well as to analyze the planned strategy for achieving good governance. This research makes Desa Hegarmanah a research object. This study used a qualitative approach with content analysis and interview methods. Based on the results of content analysis, Desa Hegarmanah produced a good governance implementation score of 83.34 (trusted), which means that the financial management results of Desa Hegarmanah can be trusted because it has implemented good governance. Obstacles encountered in the implementation of good governance are inadequate information systems, unstable signals when the weather is not good, system errors that cause delays in work, and a lack of understanding of the community in implementing activities. The strategy planned by Hegarmanah Village is to increase openness, and better and firmer implementation of the duties and functions of each village apparatus in the future in order to improve the quality of good governance.